Toward a neo-Schumpeterian theory of the firm - Sidney G. Winter (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
This paper offers a sketch of what an economic theory of the firm would look like if it were founded on the thought of Joseph Schumpeter, particularly on Chapters 1-2 of his Theory of Economic Development. Schumpeterian analysis requires an intuitively appealing and realistic conceptualization of the distinction between routine and innovative behavior, and in particular, a conceptualization relevant to complex organizations and complex tasks. It is argued that the production theory found in mainstream economics does not meet this requirement, particularly because its characterization of productive knowledge involves an overly sharp distinction between technically possible and technically impossible a distinction which has no counterpart in the realities of organizational knowledge. The main elements of a Schumpeterian view are described and contrasted with those in the mainstream view.
Keywords: 330; theory of the firm; Schumpeter; innovation; knowledge; Theorie der Unternehmung; Schumpeterismus